Everything Done with a Pure Intention is Perfect Love. Elements of Discernment of the Spirits in Santa Teresa de Jesús - Filip De Rycke (Polonia Sacra)
Saint Teresa of Ávila intrinsically connects discernment of the spirits with her principal theme of inner prayer. The main constituents of her doctrine of prayer (obedience, humility, charity, detachment) also represent key motifs in her view on discernment. From this perspective, Santa Teresa’s sparse assertions can be integrated into a coherent doctrine on discernment of the spirits, founded in her deep religious experience. Discernment emerges as the core of Christian life and the genuine way in which the Divine Friend gives light for choices that make human persons grow in virtues and in inner freedom.